2020
DOI: 10.1182/blood.2020006288
|View full text |Cite|
|
Sign up to set email alerts
|

The BTK inhibitor ibrutinib may protect against pulmonary injury in COVID-19–infected patients

Abstract: 140-HELD-420 denotes that this patient was on 140 mg/d of ibrutinib prior to hospitalization that was held upon admission; he experienced worsening hypoxia after ibrutinib was held and required mechanical ventilation, following which he was restarted on 420 mg/d of ibrutinib and showed rapid improvement in oxygenation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
302
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 281 publications
(318 citation statements)
references
References 26 publications
10
302
1
5
Order By: Relevance
“…In this line a single cell immune profiling of the temporal dynamics of ibrutinib treatment in CLL patient revealed profound modulation of the non-malignant immune cells and particularly up-regulation of inflammatory pathways in myeloid cells (45). In this context the potential benefits of early phase trials using BTK inhibitors or ruxolitinib in severe COVID-19 patients can be hypothesized to be related to overlapping target specificity and regulation of inflammatory pathways (5,6,46).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this line a single cell immune profiling of the temporal dynamics of ibrutinib treatment in CLL patient revealed profound modulation of the non-malignant immune cells and particularly up-regulation of inflammatory pathways in myeloid cells (45). In this context the potential benefits of early phase trials using BTK inhibitors or ruxolitinib in severe COVID-19 patients can be hypothesized to be related to overlapping target specificity and regulation of inflammatory pathways (5,6,46).…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of Bruton's Tyrosine Kinase (BTK) in the treatment of B-cell malignancies has been an exemplary story of functional understanding of disease pathogenesis translating to superior survival rates (1)(2)(3)(4). Moreover, inhibition of BTK is currently also being evaluated as a therapeutic strategy for patients with severe COVID-19 disease (5,6). BTK is localized in proximity of the B-cell receptor (BCR), forming a signalosome complex upon BCR activation with other BCR associated kinases (BAK); LYN, SYK, and PI3K (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…Ibrutinib has shown anti-tumor effects towards chronic lyphocytic leukemia [20][21][22][23]. It also shown growth inhibitory effect in solid cancers, but the results is limited [24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…In the clinical treatment of abnormal increases in serum IgM or neoplastic B cells, ibrutinib, which inhibits the activity of Bruton Kinase in the B cell receptor signaling pathway 70 , is now commonly used to reduce the abnormal proliferation of B cells 71,72 . Treon et al reported that the use of ibrutinib may be useful to reduce lung damage from SARS-CoV-2 infection by suppressing the number of B cells 73 . Fingolimod, as an agonist of the S1P1/3 receptor, is thought to inhibit B cell egress out of lymph node through overstimulation of the B cell S1P1/3 receptor 74,75 .…”
Section: Discussionmentioning
confidence: 99%